Amorphous alloys surpass E/10 strength limit at extreme strain rates - Zhu, Wenqing (2024)
Theoretical predictions of the ideal strength of materials range from E/30 to E/10 (E is Young's modulus). However, despite intense interest over the last decade, the value of the ideal strength achievable through experiments for metals remains a mystery. This study showcases the remarkable spall strength of Cu50Zr50 amorphous alloy that exceeds the E/10 limit at strain rates greater than 107 s-1 through laser-induced shock experiments. The material exhibits a spall strength of 11.5 GPa, approximately E/6 or 1/13 of its P-wave modulus, which sets a record for the elastic limit of metals. Electron microscopy and large-scale molecular dynamics simulations reveal that the primary failure mechanism at extreme strain rates is void nucleation and growth, rather than shear-banding. The rate dependence of material strength is explained by a void kinetic model controlled by surface energy. These findings help advance our understanding on the mechanical behavior of amorphous alloys under extreme strain rates.